2021
DOI: 10.3390/biomedicines9030320
|View full text |Cite
|
Sign up to set email alerts
|

Brown Spiders’ Phospholipases-D with Potential Therapeutic Applications: Functional Assessment of Mutant Isoforms

Abstract: Phospholipases-D (PLDs) found in Loxosceles spiders’ venoms are responsible for the dermonecrosis triggered by envenomation. PLDs can also induce other local and systemic effects, such as massive inflammatory response, edema, and hemolysis. Recombinant PLDs reproduce all of the deleterious effects induced by Loxosceles whole venoms. Herein, wild type and mutant PLDs of two species involved in accidents—L. gaucho and L. laeta—were recombinantly expressed and characterized. The mutations are related to amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Comparative analyses between the protection of animals immunized with recombinant active (rLlPLD1) or inactive (rLlPLD2) isoforms of L. laeta PLDs showed that both protocols reduced the development of dermonecrotic lesions induced by L. laeta venom at similar levels, thus reinforcing that the antigenic potential of these enzymes is not related to their activity (Catalán et al, 2011). Molecular engineering enabled the production of mutated PLDs from L. intermedia, L. laeta and L. gaucho venoms with appropriate conformational structure, but devoid of enzymatic activity, opening the possibility to apply these proteins as immunogens to the development of antivenoms or vaccines (Vuitika et al, 2016;da Silva et al, 2021). Figure 1 illustrate this potential of such toxins.…”
Section: Systemic Injury (Main) and Cutaneous Lesionmentioning
confidence: 92%
See 4 more Smart Citations
“…Comparative analyses between the protection of animals immunized with recombinant active (rLlPLD1) or inactive (rLlPLD2) isoforms of L. laeta PLDs showed that both protocols reduced the development of dermonecrotic lesions induced by L. laeta venom at similar levels, thus reinforcing that the antigenic potential of these enzymes is not related to their activity (Catalán et al, 2011). Molecular engineering enabled the production of mutated PLDs from L. intermedia, L. laeta and L. gaucho venoms with appropriate conformational structure, but devoid of enzymatic activity, opening the possibility to apply these proteins as immunogens to the development of antivenoms or vaccines (Vuitika et al, 2016;da Silva et al, 2021). Figure 1 illustrate this potential of such toxins.…”
Section: Systemic Injury (Main) and Cutaneous Lesionmentioning
confidence: 92%
“…Since the purification of large amounts of venom is one of the major hitches in this process, the first efforts to use recombinant toxins as immunogens were made. As phospholipases D (PLDs) can trigger most of the toxic effects caused by crude venom, the first studies focused on these toxins to replace the venom in the antivenom production (Chaim et al, 2006;Kusma et al, 2008;Chaves-Moreira et al, 2009, 2011Gremski et al, 2014Gremski et al, , 2020da Silva et al, 2021).…”
Section: Antivenom and Monoclonal Antibodies For The Treatment Of Loxoscelismmentioning
confidence: 99%
See 3 more Smart Citations